2017
DOI: 10.5798/dicletip.338997
|View full text |Cite
|
Sign up to set email alerts
|

Trombositten zengin Fibrinin periferik sinir iyileşmesi üzerindeki histopatolojik etkileri

Abstract: ÖzetAmaç: Sinir iyileşmesini hızlandırmak ve kalitesini artırmak için çeşitli materyallerle deneysel çalışmalar yapılmıştır. Çalışmamızın amacı trombositten zengin fibrinin (TZF) siyatik sinir iyileşmesi üzerindeki histopatolojik etkilerini deneysel rat modelinde araştırmaktır.Yazışma Adresi / Correspondence : Hasan Metineren, Dumlupınar Üniversitesi Tıp Fakültesi Evliya Çelebi Eğitim Araştırma Hastanesi İstiklal Cad. Okmeydanı Cd. 43040 Kütahya, Anahtar kelimeler: Trombositten zengin fibrin, sinir iyileşmesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The most preferred enrichment methods developed to benefit from the mentioned features of platelets are classical PRP and PRF 17 . One study examined the effects of PRF on the sciatic nerve healing model and found that PRF had an accelerating and complementary effect on peripheral nerve healing histologically 18 . In vitro studies showed that the factors released by PRP and PRF activate the adipose-derived stem cells and chemotaxis of these cells 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The most preferred enrichment methods developed to benefit from the mentioned features of platelets are classical PRP and PRF 17 . One study examined the effects of PRF on the sciatic nerve healing model and found that PRF had an accelerating and complementary effect on peripheral nerve healing histologically 18 . In vitro studies showed that the factors released by PRP and PRF activate the adipose-derived stem cells and chemotaxis of these cells 6 .…”
Section: Discussionmentioning
confidence: 99%